The Effect of Net Profit Margin (NPM) and Total Assets Turnover (TATO) Return on Assets (ROA) at PT Telekomunikasi Indonesia (Persero) Tbk for the Period of 2019-2023 - Rindu Meisya Nilamsyah; Reka Ardian Purnama (PT FORMOSA CENDEKIA GLOBAL, 2024)
Finding a correlation between ROA and the independent Factors nett profit margin and total asset turnover is the main objective of this study. The research population consists of twenty quarterly financial reports that span the years 2019–2023, sourced from PT Telekomunikasi Indonesia (Persero) Tbk. The study employs quantitative approaches using data extracted from the company's financial records and a sample strategy based on purposeful sampling. To analyse the data, statisticians employ tools like coefficient of determination, hypothesis testing, multiple linear regression, and correlation. Net Profit Margin (NPM) and Total Assets Turnover (TATO) have a partial and simultaneous effect on Return on Assets (ROA) at the 0.05 level of significance